Astrocytes in Neural Circuits: Key Factors in Synaptic Regulation and Potential Targets for Neurodevelopmental Disorders - Liu, Xing; Ying, Jun; Wang, Xifeng; Zheng, Qingcui; Zhao, Tiancheng; Yoon, Sungtae; Yu, Wen; Yang, Danying; Fang, Yang; Hua, Fuzhou (Frontiers in Molecular Neuroscience, 2021)
Astrocytes are the major glial cells in the brain, which play a supporting role in the energy and nutritional supply of neurons. They were initially regarded as passive space-filling cells, but the latest progress in the study of the development and function of astrocytes highlights their active roles in regulating synaptic transmission, formation, and plasticity. In the concept of “tripartite synapse,” the bidirectional influence between astrocytes and neurons, in addition to their steady-state and supporting function, suggests that any negative changes in the structure or function of astrocytes will affect the activity of neurons, leading to neurodevelopmental disorders. The role of astrocytes in the pathophysiology of various neurological and psychiatric disorders caused by synaptic defects is increasingly appreciated. Understanding the roles of astrocytes in regulating synaptic development and the plasticity of neural circuits could help provide new treatments for these diseases.